Seismic Waveform Tomography at Test Site with Open Chimneys. Issue 1 (January 2014) - Tran, Khiem T.; McVay, Michael; Horhota, David; Faraone, Michael; Sullivan, Brian W.
An application of two-dimensional time-domain waveform tomography to map the extent of open chimneys at a variable karstic limestone site is presented. The seismic surface wave fields were measured next to three open chimneys and inverted with a full-waveform inversion technique, which was based on a finite-difference solution of two-dimensional elastic wave equations and the Gauss–Newton inversion method. Both the compression wave (P-wave) and shear wave (S-wave) velocities were inverted independently and simultaneously to increase the credibility of the characterized profiles. The waveform analysis successfully profiled embedded low-velocity zones and highly laterally and vertically variable limestone. The inverted results are consistent with the known open chimneys observed from the ground surface. The Poisson's ratio determined from the inverted P-wave and S-wave velocities is consistent with soil types: high values of 0.3 to 0.5 for silt and clay and low values of 0.1 to 0.2 for limestone. Results show that the full-waveform inversion technique is applicable to both shallow and deep foundation design in which soil stratigraphy and variability are important. The technique is also computationally practical, because the results were all achieved in about 3 h of computer time on a standard laptop computer.